Chapter 4 'A great bliss to keep the sensation of conquest alive!' The emotional politics of the Panorama 1453 Museum in Istanbul - Bozog˘lu, Gönül (Taylor & Francis, 2020)
One aim of this chapter is to foreground the interplay of official heritage and political discourse.